Design of ring-assisted few-mode fiber with low loss for improved mode-division multiplexing. (21st September 2021) - Lu, Guangwei; Liu, Shuang; Lv, Dongyu; Chen, Mengmeng; Zhang, Zuxing
Abstract: We report a ring-assisted few-mode fiber design with large mode effective index difference (△ n eff ) and low loss. By introducing the low-index ring-assisted structure in the cladding, the effective indexes of LP11, LP21 and LP02 modes can be greatly reduced, while the effective index of LP01 mode is almost unaffected. Also, we find that introducing multiple ring-assisted structures will help reduce loss. The proposed few-mode fiber has potential application value for improved mode-division multiplexing optical fiber communication system.